Reinforcement of First Floor Reinforced Concrete Columns with Metal Ring - Docent Saydazimov Musurman Ravshanovich (Genius Journals, 2023)
This article provides a calculation of a metal clip used as a reinforcement for reinforced concrete columns of reconstructed buildings. In addition, information is produced on the materials used and the technology for performing reinforcement.
Keywords: Metal clip; square; spacers